A bright future for micro-LED displays - Vineeth K. Bandari; Oliver G. Schmidt (Light: Science & Applications)
Abstract The development of GaN-based Micro-LED arrays achieving brightnesses exceeding 107 nits and high-density micro-displays with up to 1080×780 pixels marks a true breakthrough in the field. This breakthrough is a result of mastering a combination of long-standing challenges comprising wafer-scale high-quality epitaxial growth, sidewall passivation, efficient photon extraction, and elegant bonding technologies, and promises significant advantages for augmented and virtual reality devices, wearables, and next-generation consumer electronics.